Laser-driven metal alteration for glucose detection sensor - Kondrateva, A.; Babyuk, V.; Strekalovskaya, D.; Filatov, L.; Gabdullin, P.; Kvashenkina, O.; Prokopenko, Y.; Gruzdev, A.; Petruhno, K.; Kuznetsov, A. (Peter the Great St. Petersburg Polytechnic University, 2021)
In this work, an experimental comparison of the laser-driven alteration of nickel, copper, and steel surface efficiency was carried out. The selection of the material most suitable for non-enzymatic measurement of the glucose amount in the medium was carried with respect to surface modification efficiency. The electrooxidative activity of the fabricated structures with a modified surface was investigated with respect to the glucose addition to a 0.1 M solution NaOH by potentiostatic method. The modified active NiO layer allows us the amperometric determination of glucose in the concentration range from 10 µM to 1.5 mM with sensitivity is higher than 10 µA/(mM·cm2) and the detection limit is not less than 5 µM. The proposed technology allows the manufacture of electrodes for non-enzymatic determination of glucose in alkaline solutions.